2017
DOI: 10.3855/jidc.9257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of children admitted with fever in emergency department with or without sepsis

Abstract: Introduction: Sepsis is a major cause of childhood death worldwide. In developing countries, epidemiological data about sepsis is scarce. This study describes and compares the frequency of etiological agents and initial sites of infection in children with or without sepsis, identifying risk factors and assessing outcomes. Methodology: Clinical and demographic data from patients < 13 years of age with reported fever in a pediatric emergency department were collected and registered in forms. Patients were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Present findings are similar to the study of de Santana et al In his study, out of 254 patients UTIs was seen in 18 (7.1%) cases. 9 In present series, leptospirosis was diagnosed in 78 children (12.6%) with fever. Cruz et al in 1994 studied 188 children with prolonged fever, 23 children (12.2%) had serological evidence of leptospirosis.…”
Section: Discussionmentioning
confidence: 56%
“…Present findings are similar to the study of de Santana et al In his study, out of 254 patients UTIs was seen in 18 (7.1%) cases. 9 In present series, leptospirosis was diagnosed in 78 children (12.6%) with fever. Cruz et al in 1994 studied 188 children with prolonged fever, 23 children (12.2%) had serological evidence of leptospirosis.…”
Section: Discussionmentioning
confidence: 56%
“…Similar results were seen in various studies done in the Western world on febrile children presenting to the ED which showed pneumonia (43.7%) as most common cause of fever in <13 years old febrile children, and others being diarrhoea (17.3%) and cellulitis/adenitis (13%). [30][31][32] Finkelstein, et al reported similar findings in 3-36 months old infants in the US. 5 Studies done in Indian children also showed respiratory and the gastrointestinal illnesses as the most common diagnosis in febrile children.…”
Section: Discussionmentioning
confidence: 62%
“…The most reported SDOH categories were preadmission nutritional status (35.8%, 38/106) (17–52) and race/ethnicity (18.9%, 20/106) (21, 22, 25, 29, 33, 42, 45, 51, 53–64) (Table 1). For nutrition, 38 articles reported 24 different measures reflecting nutrition, weight, height, or body mass index.…”
Section: Resultsmentioning
confidence: 99%